Indonesia’s Political Position on the Protection Policy of Migrant Workers in ASEAN - Linda Dwi Eriyanti; Muhammad Hadi Makmur; Diah Ayu Intansari (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2022)
As a sending country of migrant workers in ASEAN, Indonesia has a weaker bargain than the receiving countries. This is in line with the thoughts of Marxist Feminism arguing that within the structure of a capitalist society, the owners of the capital, in which context are the receiving countries, have more power to control the factors of production. Indonesia has weak bargaining power, so Indonesia's political position in protecting its migrant workers in ASEAN has never changed. It has always been a follower country. One instance of the studies investigating the position was conducted by Amelia (2013) with their political position indicator. The researcher divides the country’s political position into the first country, the follower country, the satellite country, and the independent country. This study aims to examine Indonesia’s political position in the protection policies of Indonesian migrant workers in ASEAN. This study is framed by qualitative method with case study and interpretative analysis. The results of this study indicate that Indonesia’s political position on its migrant worker protection policies can be categorized into a follower country.